2022
DOI: 10.1038/s41598-022-15600-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial evaluation of animal health care accessibility and veterinary shortage in France

Abstract: The decrease in the supply of veterinary healthcare in France adversely affects health of food-producing animals. In a One Health perspective, the health of people, animals and their shared environment are interconnected, and adequate supply of veterinary healthcare is required to ensure public health. Prevention of outbreaks and zoonotic diseases that may impact public health mobilizes a set of public policies, including strengthening veterinary workforce. These policies should be informed by quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The two-step floating catchment area(2SFCA) method is a widely used approach for evaluating the accessibility of facilities or services [ 18 , 19 , 23 ]. Compared to other methods (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The two-step floating catchment area(2SFCA) method is a widely used approach for evaluating the accessibility of facilities or services [ 18 , 19 , 23 ]. Compared to other methods (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Between 2016 and 2020, the percentage of veterinarians in the food animal sector (FAS) plummeted by 18% in France [ 1 ]. The definition and location of a veterinarian shortage in France has been mapped, enabling public and private authorities to establish appropriate measures to address this concern, as done for physician shortage [ 2 ]. France is not unique when it comes to a veterinarian shortage.…”
Section: Introductionmentioning
confidence: 99%
“…Floating catchment models have only rarely been used to evaluate access to veterinary care [ 31 ]. One recent paper used the E2SFCA to suggest a method to optimize rabies vaccination site locations in Southeastern Brazil [ 31 ] and another used the 2SFCA to evaluate spatial access to large animal veterinarians in a region of France [ 33 ]. In a review of the literature, the only other paper found to use any form of this method in veterinary care was a paper published in German relating to access to care for companion animals in Switzerland using a FCA model [ 34 ].…”
Section: Introductionmentioning
confidence: 99%